Gulf Stream density structure and transport during the past millennium - Lund, D. C.; Lynch-Stieglitz, J.; Curry, W. B. (Nature, 2006)
The Gulf Stream transports approximately 31 Sv (1 Sv = 10(6) m(3) s(-1)) of water and 1.3 x 10(15) W of heat into the North Atlantic ocean. The possibility of abrupt changes in Gulf Stream heat transport is one of the key uncertainties in predictions of climate change for the coming centuries. Given the limited length of the instrumental record, our knowledge of Gulf Stream behaviour on long timescales must rely heavily on information from geologic archives. Here we use foraminifera from a suite of high-resolution sediment cores in the Florida Straits to show that the cross-current density gradient and vertical current shear of the Gulf Stream were systematically lower during the Little Ice Age (ad approximately 1200 to 1850). We also estimate that Little Ice Age volume transport was ten per cent weaker than today's. The timing of reduced flow is consistent with temperature minima in several palaeoclimate records, implying that diminished oceanic heat transport may have contributed to Little Ice Age cooling in the North Atlantic. The interval of low flow also coincides with anomalously high Gulf Stream surface salinity, suggesting a tight linkage between the Atlantic Ocean circulation and hydrologic cycle during the past millennium.
Lund, David CLynch-Stieglitz, JeanCurry, William BengResearch Support, U.S. Gov't, Non-P.H.S.England2006/12/01 09:00Nature. 2006 Nov 30;444(7119):601-4.